Age Restriction for Job Application from a Human Rights Perspective - Ni Wayan Ella Apryani (Journal of Law, Politic and Humanities, 2024)
Age restriction in applying for a job becomes an essential issue when it causes discriminatory consequences for job seekers, especially if it is caused by the provisions of Article 35 paragraph (1) of Law Number 13 of 2003 concerning Manpower which is considered vague so as to provide a legal loophole for discriminatory actions in providing employment opportunities by employers. The purpose of this study is to examine the vagueness of norms in Article 35 paragraph (1) of the Manpower Law and human rights issues in limiting the age of applying for a job. Examining the problems from the existing laws and doctrines, this research uses normative research methods with the focus of the study is on the norms governing the age restriction of job applications in terms of human rights perspectives and concepts. The results show that the purpose of Article 35 para-graph (1) does not provide an opportunity for discrimination but as a form of flexibility related to determining labor needs. The age limit for applying for a job is not a violation of human rights when viewed from the perspective of the main principles of human rights. The determination of age limit criteria is not specifically regulated and is not prohibited by positive legal provisions in Indonesia so that it cannot be said to be a form of discrimination in providing employment opportunities.